Flexural, thermal and dynamic mechanical properties of date palm fibres reinforced epoxy composites - Gheith, Mohamed Hamdy; Aziz, Mohamed Abdel; Ghori, Waheedullah; Saba, Naheed; Mohammad Asim; Jawaid, Mohammad; Alothman, Othman Y. (Elsevier Editora, 2019)
The aim of the present study is to improve the flexural, thermal stability and dynamic mechanical properties of epoxy composites by reinforcing date palm fibres (DPF) at different loading (40%, 50% and 60% by wt.) and to evaluate the best loading through hand lay-up technique. Three point bending dynamic properties in terms of storage modulus (E′), loss modulus (E″) damping factor, Cole–Cole plot and thermal properties were analyzed by dynamic mechanical and thermogravimetric analyser, respectively. Flexural test results show that loading of 50% DPF increases both the flexural strength and modulus of pure epoxy composites from 26.15 MPa to 32.64 MPa and 2.26 GPa to 3.28 GPa, respectively. TGA results revealed that reinforcement of DPF in epoxy composites also improves the thermal stability and residual content. The residual content of epoxy (9.58%), 40% DPF/epoxy (12.51%), 50% DPF/epoxy (19.8%) and for 60% DPF/epoxy composites (15.2%) was noted, revealing that 50% DPF/epoxy composites confers the best result. Incorporation of DPF into epoxy also improves the E′ and E″ but 50% DPF show more remarkable improvement compared to 40% and 60% DPF loading. Moreover, damping factor decreases considerably by the reinforcement of DPF and are found lowest for 50% DPF/epoxy composites among all composites. Drawn Cole–Cole plot also suggests the existence of certain heterogeneity in DPF/epoxy composites compared to homogenous nature of epoxy composites. We concluded that 50% DPF loading is the ideal loading to enhanced flexural, thermal stability and dynamic properties of epoxy composites.